ANALISIS TINGKAT LIKUIDITAS PADA PT. TELEKOMUNIKASI INDONESIA Tbk - KURANTA, SEFLIN SINTIA; MONTOLALU, JHONNY; TAMPI, DOLINA L. (JURNAL ADMINISTRASI BISNIS, 2016)
ABSTRACT : The purpose of this study was to analyze the level of liquidity PT.Telekomunikasi Indonesia Tbk. If the company has good liquidity, the companywas able to survive and complete with other companies.The method used in this research is descriptive quantitative method usingliquidity ratio to Analyze the level of liquidity of the company. Based on the resultsof the analysis carried out showed that the level of liquidity PT. TelekomunikasiIndonesia Tbk has a Current Ratio percentage value of 113.98% in the years 2011-2015. Quick Ratio values in the years 2011-2015 have a percentage of the value of107.8%. Cash Ratio values in the years 2011-2015 have a value percentage of57.9%.PT. Telekomunikasi Indonesia Tbk have good liquidity in the years 2011-2015. Telekomunikasi Indonesia Tbk have a favorable cash criteria from theperspective of anyone because it is not too high and not too low.Company’sliquidity is maintained and cultivated for the future could continue to affort to meetthe level of liquidity with a good percentage.Keywords : Liquidity, Current Ratio, Quick Ratio, Cash Ratio.